Medication Intake, Perceived Barriers, and Their Correlates Among Adults With Type 1 and Type 2 Diabetes: Results From Diabetes MILES – The Netherlands - Hogervorst, Stijn; Adriaanse, Marce C.; Hugtenburg, Jacqueline G.; Bot, Mariska; Speight, Jane; Pouwer, Frans; Nefs, Giesje (Frontiers in Clinical Diabetes and Healthcare, 2021)
Purpose: The purpose of this study is to investigate medication intake, perceived barriers and their correlates in adults with type 1 or type 2 diabetes. Methods: In this cross-sectional study, 3,383 Dutch adults with diabetes (42% type 1; 58% type 2) completed the 12-item ‘Adherence Starts with Knowledge’ questionnaire (ASK-12; total score range: 12-60) and reported socio-demographics, clinical and psychological characteristics and health behaviours. Univariable and multivariable logistic regression analyses were used. Results: Adults with type 1 diabetes had a slightly lower mean ASK-12 score (i.e. more optimal medication intake and fewer perceived barriers) than adults with non-insulin-treated type 2 diabetes. After adjustment for covariates, correlates with suboptimal intake and barriers were fewer severe hypoglycaemic events and more depressive symptoms and diabetes-specific distress. In type 2 diabetes, correlates were longer diabetes duration, more depressive symptoms and diabetes-specific distress. Conclusions: Adults with type 1 diabetes showed slightly more optimal medication intake and fewer perceived barriers than adults with non-insulin treated type 2 diabetes. Correlates differed only slightly between diabetes types. The strong association with depressive symptoms and diabetes-specific distress in both diabetes types warrants attention, as improving these outcomes in some people with diabetes might indirectly improve medication intake.